Proc. 17th Int. Conf. On High Pressure in Semiconductor Physics &Amp; Workshop on High-Pressure Study on Superconducting 2017
DOI: 10.7567/jjapcp.6.011106
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity measurements under high pressure for Nd3.5Sm0.5Ni3O8

Abstract: Nd3.5Sm0.5Ni3O8 is a candidate for high-Tc superconductor, due to the close structural and electrical similarities with high-Tc cuprates. In electrical resistivity measurement, Nd3.5Sm0.5Ni3O8 shows a semiconducting behavior. However, by intercalation and subsequent deintercalation treatments with sulfur, Nd3.5Sm0.5Ni3O8 displays metallic behavior down to 20 -40 K, followed by the weak semiconducting tendency at lower temperatures. In this study, the electrical resistivity measurements under high pressures up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…NMR measurements revealed 2D antiferromagnetic fluctuations [22], and both magnetic and charge-ordering phenomena were inferred from X-ray and neutron-diffraction (ND) measurements [23,24]. Semiconducting behavior has also been reported for Nd3.5Sm0.5Ni3O8, with a trend to increasing metallicity under pressure [25].…”
mentioning
confidence: 97%
“…NMR measurements revealed 2D antiferromagnetic fluctuations [22], and both magnetic and charge-ordering phenomena were inferred from X-ray and neutron-diffraction (ND) measurements [23,24]. Semiconducting behavior has also been reported for Nd3.5Sm0.5Ni3O8, with a trend to increasing metallicity under pressure [25].…”
mentioning
confidence: 97%
“…Recently, we found that Nd 3.5 Sm 0.5 Ni 3 O 8 exhibits metallic behavior down to around 20 -40 K after intercalation and subsequent deintercalation treatment with sulfur (called as S-treatment hereafter) [18,19]. The synchrotron X-ray diffraction study suggests that the appearance of metallic behavior upon S-treatment is associated with the removal of additional apical oxygen [20], like the situation of T'-type high-T c cuprates.…”
Section: Introductionmentioning
confidence: 99%